C-Glycosylation in platinum-based agents: a viable strategy to improve cytotoxicity and selectivity. Issue 11 (10th October 2018) - Cucciolito, Maria Elena; De Luca Bossa, Ferdinando; Esposito, Roberto; Ferraro, Giarita; Iadonisi, Alfonso; Petruk, Ganna; D'Elia, Luigi; Romanetti, Claudia; Traboni, Serena; Tuzi, Angela; Monti, Daria Maria; Merlino, Antonello; et al.
Abstract : The glycosylation of five-coordinate Pt(ii ) compounds through a Pt–C linkage can be a very effective strategy for attacking cancer cells, while preserving the survival of the healthy ones. Abstract : Novel coordinatively saturated platinum(ii ) compounds bearing C-linked carbohydrates were synthesized and characterized. The complexes exhibit bipyramidal trigonal geometry with a bidentate nitrogen ligand and ethylene in the equatorial plane. The axial positions are occupied by a halide ligand X and ad -galactose ord -glucose derivative, linked either via C1 or C6. The compounds were designed for evaluation of the biological activity because they combine the steady coordinative saturation, the beneficial action of the modular sugar moiety and the organometallic nature of the Pt-sugar linkage, which is expected to be stable in the biological media, until the target is reached. The newly synthesized molecules were stable in mixed DMSO/aqueous solvents, able to bind DNA in vitro and exhibited a selective cytotoxic activity on cancer cells through apoptosis activation.